Peculiarities of logical and methodological approaches to the qualifying paper development by ecologist and chemmytologist - Павлюх, Л. І. (Proceedings of National Aviation University (archive), 2013)
Algorithm of the qualifying paper development is presented. Periodical publications on ecological and chemmytological directions are systematized